2015
DOI: 10.2147/opth.s71387
|View full text |Cite
|
Sign up to set email alerts
|

Vitreous flow rates through dual pneumatic cutters: effects of duty cycle and cut rate

Abstract: PurposeWe aimed to investigate effects of instrument settings on porcine vitreous flow rates through dual pneumatic high-speed vitrectomy probes.MethodsThe CONSTELLATION® Vision System was tested with 250, 450, and 650 mmHg of vacuum using six ULTRAVIT® vitrectomy probes of each diameter (25+®, 25, 23, and 20 gauge) operated from 500 cuts per minute (cpm) up to 5,000 cpm. Duty cycle modes tested included biased open, 50/50, and biased closed. Flow rates were calculated by assessing the change in weight of porc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 8 publications
0
26
0
1
Order By: Relevance
“…We adopted both BSS and AV in our experiments, as representative of the liquefied vitreous (BSS) and of the vitreous in its gel phase (AV) in order to reproduce as closely as possible, the working conditions during the vitrectomy. Other authors in the past tested vitreous cutters with non-Newtonian viscoelastic fluids, in particular using egg albumen 2 , 13 17 or porcine eyes 5 , 15 , 18 ; however, information on the rheologic properties of the fluids were not provided. Using AV, we could test the rheology of the fluid and tune it in such a way that is has properties similar to those of the healthy vitreous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopted both BSS and AV in our experiments, as representative of the liquefied vitreous (BSS) and of the vitreous in its gel phase (AV) in order to reproduce as closely as possible, the working conditions during the vitrectomy. Other authors in the past tested vitreous cutters with non-Newtonian viscoelastic fluids, in particular using egg albumen 2 , 13 17 or porcine eyes 5 , 15 , 18 ; however, information on the rheologic properties of the fluids were not provided. Using AV, we could test the rheology of the fluid and tune it in such a way that is has properties similar to those of the healthy vitreous.…”
Section: Discussionmentioning
confidence: 99%
“… 13 17 Experiments on vitreous from animal eyes have also been performed. 5 , 15 , 18 The above studies focused on the measurement of the flow rate and its dependency on the working conditions. In recent years Particle Image Velocimetry (PIV) measurements have been introduced to measure the flow field around the tip of vitreous cutters in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…A better surgical setting has enhanced flow stability and minimised vitreous turbulences, especially when the vitrectomy probe passes from the vitreous to the balanced salt solution or a dense vitreous base. 17 All together miniaturising and improving vitrectomy systems reduce retinal traction and thereby the risk of iatrogenic retinal breaks. 18,19 In this study, using a 25-gauge system, we found a rate of 8.3% of intraoperative retinal breaks at the end of vitrectomy that could be even overestimated, as any suspicious appearance was considered as an opening and treated.…”
Section: Discussionmentioning
confidence: 99%
“…6; Additional file 2: video 2). This allows the DC to be controlled independently of the cut rate [19, 24, 3739] with customized modes: “port biased open” or core mode (the port remains open for the majority of time), 50/50 mode (the port is open 50% of the time) and “biased closed” or shave mode (the port remains closed for the majority of time). Therefore, besides the cut rate and vacuum/aspiration levels, the surgeon can count on another variable in order to control the flow rate.…”
Section: Vitrectomy Cuttersmentioning
confidence: 99%